Gambaran Pengetahuan Remaja Tentang Perawatan Organ Reproduksi - Mareti, Silvia; Amalia Azmy, Restu; Mardiyah, Adiyati (REAL in Nursing Journal, 2023)
Background: Treatment of the reproductive organs is important as a solution to prevent sexually transmitted diseases. Every teenager must be equipped with information on how to maintain the health of the reproductive organs so as to avoid diseases that can damage the ability of the reproductive organs. Aims: describe the knowledge of adolescents about the care of the reproductive organs. Methods: This research is a type of quantitative descriptive research with a cross sectional research design. The research subjects were 172 students of SMAN 2 and SMAN 4 Pangkalpinang City. The instrument used was a reproductive health knowledge questionnaire. Data analysis was performed using computerization and univariate analysis. Results: the results showed that as many as (91.3%) of adolescents knew how to clean the genital area after defecating, as many as (65.1%) of adolescents knew how to keep the pubic area moist during activities and as many as (94.2%) of adolescents knew how to maintain cleanliness of the pubic area during menstruation. Conclusion: knowledge about how to clean the genital area after defecation is considered the least information that is known to adolescents. Suggestions that can enrich reproductive health socialization materials for adolescents adapted to current scientific and technological developments.Keywords: adolescent knowledge, reproductive health, care of reproductive organs